D-REHABIA: A Drug Addiction Recovery Through Mobile Based Application - Galabada, S.S.G.; Wijethunga, H.M.; Somasiri, L.U.; Dayananda, H.M.; Nugaliyadde, A.; Thelijjagoda, S.; Rajasuriya, M. (Sri Lanka Institute of Information Technology, 2016)
Drug addiction has become a major issue in the world. There are certain governmental and nongovernmental organizations which provide variousprograms to prevent, recover and rehabilitate drug addicts. The patients who are in the recovery process havea higher tendency of relapsing after being released to the society. The objective of this research is to produce a mobile based Drug Recovery Application and prevent patients from relapsing during the recovery process and to involve both family and rehabilitation center to the recovery of the patient. In order to accomplish this objective, the application contains an artificial intelligent assistant which will guide/help the patient regarding issues occurred during the recovery process, a location tracking mechanism to identify the movements of the patient and possible high risk places where drugs can circulate, a voice analysis mechanism to analyze the voice of the patient and identify emotional states which might cause the patient to relapse and treatments to reduce the stress, anxiety and depression level of the patient. The field of drug rehabilitation has been barely addressed via a proper technological solution, hence the system implemented as the result of this research can be effectively used for the recovery of the patient.
Keywords: D-REHABIA; Drug Addiction; Recovery; Mobile Based Application